Time multiplexed super resolution of multicore fiber endoscope using multimode fiber illumination patterns - Herman, Oran; Wagner, Omer; Shabairou, Nadav; Zalevsky, Zeev (Optical fiber technology, 2020)
•Multi-core fiber resolution limit can be surpassed using super resolution techniques.•Multi-mode fiber used for illumination can be beneficial for improving resolution.•Lensless endoscopes can be simple and effective. Optical fibers’ flexible mechanics and thin diameter makes them highly desirable for imaging in the field of optical endoscopy. Their ability to efficiently convey light towards an external imaging sensor outside the subject’s body, allows an optical fiber-based system to achieve high-resolution optical imaging from inside the body. Typically, commercial systems consist of a single core illumination fiber and a multi-core imaging fiber. Each of the cores acts like a fiber in itself, and serves as a single pixel in the final image. To eliminate core-to-core light coupling, each core has to be separated from its neighbor with a sufficient length. This creates a pixelated image having reduced resolution for small overall fiber diameter and it is being damaged by pixelization artifacts. In this paper we describe a method that uses a multimode illumination fiber to project different high-resolution patterns on the inspected sample. Images of the different patterns illuminating the inspected sample are then taken using a multi-core imaging fiber, and a post processing algorithm eliminates the pixelization effects and increases the imaging resolution. The advantage of the proposed concept is that the overall endoscope can have overall very thin diameter which consists from a very thin low-resolution multi-core fiber and a diameter of a projection multi-mode fiber which is also being very thin.